Epidemiological description of and response to a large yellow fever outbreak in Edo state Nigeria, September 2018 - January 2019 - E. Nwachukwu William; John Oladejo; Chinenye Mary Ofoegbunam; Chimezie Anueyiagu; Festus Dogunro; Sandra Okwudili Etiki; Botson Iliya Dachung; Celestina Obiekea; Bukola Aderoju; Kayode Akanbi; Idayat Temitope Adeyemi; Gboyega Adekunle Famokun; et al. (BMC, 2022)
Abstract Background Edo State Surveillance Unit observed the emergence of a disease with "no clear-cut-diagnosis", which affected peri-urban Local Government Areas (LGAs) from September 6 to November 1, 2018. On notification, the Nigeria Centre for Disease Control deployed a Rapid Response Team (RRT) to support outbreak investigation and response activities in the State. This study describes the epidemiology of and response to a large yellow fever (YF) outbreak in Edo State. Methods A cross-sectional descriptive outbreak investigation of YF outbreak in Edo State. A suspected case of YF was defined as "Any person residing in Edo State with acute onset of fever and jaundice appearing within 14 days of onset of the first symptoms from September 2018 to January 2019". Our response involved active case search in health facilities and communities, retrospective review of patients' records, rapid risk assessment, entomological survey, rapid YF vaccination coverage assessment, blood sample collection, case management and risk communication. Descriptive data analysis using percentages, proportions, frequencies were made. Results A total of 209 suspected cases were line-listed. Sixty-seven (67) confirmed in 12 LGAs with 15 deaths [Case fatality rate (CFR 22.4%)]. Among confirmed cases, median age was 24.8, (range 64 (1-64) years; Fifty-one (76.1%) were males; and only 13 (19.4%) had a history of YF vaccination. Vaccination coverage survey involving 241 children revealed low YF vaccine uptake, with 44.6% providing routine immunisation cards for sighting. Risk of YF transmission was 71.4%. Presence of Aedes with high-larval indices (House Index ≥5% and/or Breteau Index ≥20) were established in all the seven locations visited. YF reactive mass vaccination campaign was implemented. Conclusion Edo State is one of the states in Nigeria with the highest burden of yellow fever. More males were affected among the confirmed. Major symptoms include fever, jaundice, weakness, and bleeding. Majority of surveillance performance indicators were above target. There is a high risk of transmission of the disease in the state. Low yellow fever vaccination coverage, and presence of yellow fever vectors (Ae.aegypti, Ae.albopictus and Ae.simpsoni) are responsible for cases in affected communities. Enhanced surveillance, improved laboratory sample management, reactive vaccination campaign, improved yellow fever case management and increased risk communication/awareness are very important mitigation strategies to be sustained in Edo state to prevent further spread and mortality from yellow fever.